Desarrollo de una aplicación web y móvil utilizando la metodología agile inception, para la gestión de servicios de trabajos informales en Riobamba. - Guaman Santiago, Edwin Alexis (2022)
This research aims to develop a web and mobile application using the Agile Inception methodology, for the management of informal work services in Riobamba; its main feature is to improve the management of informal work through data records of all unemployed people and those who are looking for workers, achieving labor contact between the employee and the employer through WhatsApp, an instant application; achieving more efficient and secure communication between the employee and the employer. The Agile Inception methodology was used to plan the application development by using the Visual Studio Code tool. Mongo DB was employed for the programming of the web application. Database and programming for the mobile application were done in the Ionic framework 6 where the designs, prototypes, information verification, and resource planning were carried out having as a result the Trabaja conmigo application, thanks to the methodology used, involving users to have a better interaction, and satisfying their working needs. The web and mobile application, Trabaja Conmigo, was widely accepted by users who signed up for the application and evaluated it as something new and important. They also emphasized that the interface is efficient in the search process and contacts a job immediately. Therefore, it can be ensured that the Trabaja Conmigo application is useful for society and significant nowadays